Attack Pattern and Reproductive Ecology of Tomicus brevipilosus (Coleoptera: Curculionidae) on Pinus yunnanensis in Southwestern China. Issue 1 (15th April 2015) - Chen, Peng; Lu, Jun; Haack, Robert A.; Ye, Hui
Abstract : Tomicus brevipilosus (Eggers) (Coleoptera: Curculionidae, Scolytinae) was recently discovered as a new pest of Yunnan pine ( Pinus yunnanensis Franchet) in Yunnan Province in southwestern China. However, little was known on its reproductive biology and pattern of trunk attack on Yunnan pine. The objectives of this study were to better understand the reproductive biology of T. brevipilosus by investigating the seasonality of trunk attacks by parent adults for the purpose of reproduction (i.e., breeding attacks) and the within-tree pattern of these attacks. Our results showed that T. brevipilosus breeding attacks in P. yunnanensis generally started in early March and ended in early June in Anning County, Yunnan. T. brevipilosus exhibited two general patterns of infestation. From early March to mid-April, T. brevipilosus bred preferentially in the trunks of Yunnan pine trees that were already infested by Tomicus yunnanensis Kirkendall and Faccoli and Tomicus minor (Hartig), colonizing spaces along the trunk (mostly in the mid- and lower trunk) that were not already occupied by the other two Tomicus species. Later, from about mid-April to early June, when there were no Yunnan pine trees newly infested by T. yunnanensis and T. minor, T. brevipilosus attacked Yunnan pine by itself, infesting the lower parts of the trunk first and then infesting progressively upward along the trunk into the crown. Infestation by T. brevipilosus extends the total period that P. yunnanensis trees are under attack by Tomicus beetles in southwestern China, which helps explain why Yunnan pine has suffered high levels of tree mortality in recent decades.